Osteocytes contribute via nuclear receptor PPAR-alpha to maintenance of bone and systemic energy metabolism - Chougule, Amit; Baroi, Sudipta; Czernik, Piotr J.; Crowe, Emily; Chang, Mi Ra; Griffin, Patrick R.; Lecka-Czernik, Beata (Frontiers in Endocrinology, 2023)
A concept that bone and energy metabolism are integrated by common regulatory mechanisms is broadly accepted and supported by multiple evidence. This includes well characterized role of PPARγ nuclear receptor which is a denominator of energy metabolism and bone metabolism. Not much however is known on the role of PPARα nuclear receptor in bone, a major regulator of lipid metabolism in other organs. By employing side-by-side comparison study of mice with global PPARα deficiency (αKO) and mice with osteocyte-specific PPARα deficiency (αOTKO) we were able to dissect different activities of PPARα in the skeleton of local and systemic significance. We found that in osteocytes PPARα controls large number of transcripts coding for signaling proteins and osteocyte secretome which regulates development of bone marrow adipose tissue and peripheral fat metabolism. We have also demonstrated that PPARα in osteocytes controls their bioenergetics and mitochondrial response to stress, which constitutes up to 40% of total PPARα contribution to the global energy metabolism. Similarly to αKO mice, the metabolic phenotype of αOTKO mice, males and females, is age dependent. In younger mice, osteocyte metabolism contributes positively to the global energetics, however with aging high energy phenotype reverts to low energy phenotype and obesity, suggesting longitudinal negative effect of impaired lipid metabolism and mitochondrial dysfunction in osteocytes deficient in PPARα. However, bone phenotype in not affected in αOTKO mice except an increased volume of marrow adipose tissue in males. In contrast, global PPARα deficiency in αKO mice leads to enlarged bone diameter with proportionally increased number of trabeculae and enlarged marrow cavity, and altered differentiation of hematopoietic and mesenchymal marrow cells toward osteoclast, osteoblast and adipocyte lineages, respectively. Taking together, PPARα role in bone is multileveled and complex. In osteocytes, PPARα controls their bioenergetics which significantly contributes to the systemic energy metabolism and their endocrine/paracrine function controlling marrow adiposity and peripheral fat metabolism.